Lightweight anti-radiation metal nano-material for SAR (Synthetic Aperture Radar) load and preparation method thereof
By using methods for preparing nano-silica-graphene composites and nano-TiC-TiB2 particles, the problem of improving the service performance of carbon steel was solved, achieving lightweighting and radiation resistance of the SAR payload system.
Patent Information
- Application Number
- CN202411313032.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-10
AI Technical Summary
Existing technologies cannot significantly improve the service performance of carbon steel in a short period of time through traditional means, and cannot meet the requirements of lightweight and radiation resistance of SAR payload systems.
Carbon steel nanomaterials were prepared by using nano-silica-graphene composites and nano-TiC-TiB2 particles as fillers, and high-temperature reduction and ultra-fast cooling technology to form doped structures and refine the microstructure, thereby improving radiation resistance.
It achieves lightweighting and improved radiation resistance of carbon steel, reducing density while improving mechanical properties to meet the requirements of SAR payload systems.
Smart Images

Figure BDA0005051256870000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metallurgy, and in particular to a lightweight radiation-resistant metal nano material for SAR payload and a preparation method thereof. Background Art
[0002] Research on lightweight SAR payloads. A SAR payload system of 100 kg was developed through the application of new materials, new technologies and new system architecture. On the one hand, it can reduce the demand for satellite platforms, so that micro-nano satellites can meet the platform requirements of SAR payload systems; on the other hand, it can greatly reduce the launch cost, reducing the launch cost by an order of magnitude to tens of millions. In addition, during the use of the materials of the SAR payload system, reducing the loss is one of the research purposes. Because the equipment is expensive and difficult to maintain, developing new materials to improve the overall radiation resistance is also a top priority.
[0003] Among many steel materials, carbon steel is widely used in automobiles, aerospace, infrastructure construction and various machinery manufacturing industries due to its excellent service performance. With the rapid development of economy and technology, the upgrading of traditional industries and the rise of emerging industries have placed higher requirements on the performance of steel materials. However, the traditional strengthening and toughening methods such as optimizing heat treatment processes and changing the ratio of alloy elements to improve the performance of carbon steel have encountered bottlenecks and cannot make breakthrough progress in a short period of time. Therefore, it is urgent to propose a new, flexible, practical, low-cost method that can significantly improve the service performance of carbon steel. The present invention uses nano-scale fillers to modify carbon steel, improve the target performance while ensuring the mechanical properties of the carbon steel itself, so as to meet the requirements of the project system. Summary of the invention
[0004] The purpose of the present invention is to provide a lightweight radiation-resistant metal nanomaterial for SAR payload and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a lightweight radiation-resistant metal nanomaterial for SAR payload, wherein the metal nanomaterial is a carbon steel nanomaterial prepared by using nano-silicon dioxide-graphene composites and nano-TiC-TiB2 particles as fillers.
[0006] Furthermore, the nano-silicon dioxide-graphene composite is prepared by reducing tetraethyl orthosilicate to form a silicon dioxide sol and a composite with graphene, and is reduced to a silicon semiconductor at a high temperature when preparing the carbon steel material.
[0007] Furthermore, a method for preparing a lightweight radiation-resistant metal nanomaterial for SAR payload includes the following preparation steps:
[0008] (1) adding 1 part of ethyl orthosilicate to 8-10 parts of ethanol aqueous solution with a mass fraction of 90% ethanol, then adding 0.5-0.7 parts of a catalyst, and reacting at a temperature of 40° C. with a power of 30 kHz and a stirring speed of 200 rpm for 1 hour to obtain a nano-silica sol; adding 0.5-1.5 parts of graphene to 10 parts of the nano-silica sol, and stirring at a power of 30 kHz and a speed of 200 rpm for 1 hour to disperse evenly to obtain a mixed solution, and freeze-drying until no more weight loss occurs to obtain a nano-silica-graphene composite;
[0009] (2) Al powder, Ti powder and B4C powder with a purity of 99.5% were placed in a drying oven at a temperature of 950°C in a mass ratio of 74:20:8 for 24 hours, and then the dried mixed powder was ball-milled and activated using a high-energy ball mill. 5 mm quartz stone was added as a ball-milling medium, the ball-to-material ratio was 10:1, the ball mill speed was 60 rpm, the forward and reverse switching time was 15 minutes, and the ball milling was carried out for 48 hours; the mixed powder was taken out, wrapped with aluminum foil, and the coated mixed powder was pressed into a cylindrical block on a hydraulic press. The block size was The cylindrical blank is wrapped with graphite paper, and then placed in a graphite mold for in-situ reaction of the pressed green sheet sintering, and the graphite mold is placed in a high vacuum thermal explosion-hot pressing furnace; the temperature in the furnace is heated to 500°C, kept warm for 10 minutes, and then continued to heat to 900°C, kept warm for 10 minutes, and then an axial pressure of 40-60MPa is applied to the pressed green sheet, and the pressure is maintained for about 25 seconds; then the heating device is turned off, the vacuum in the furnace is maintained, and the furnace is cooled to room temperature to obtain an aluminum-based intermediate alloy containing nano-TiC-TiB2 particles;
[0010] (3) No. 35 steel and cold plate are placed in a 1000kg medium frequency induction furnace at a mass ratio of 3:5, heated to 1660°C, kept warm for 2 hours, and molten steel is obtained. Then, the ladle is preheated in advance at a preheating temperature of 300°C. Before pouring the ladle, an aluminum-based master alloy containing nano-TiC-TiB2 particles accounting for 0.1-0.3% of the mass of No. 35 steel is crushed by a planer and evenly spread on the bottom of the ladle, and then evenly sprinkled into the ladle at a mass ratio of 0.04-0.04 8% by mass ratio of nano-silicon dioxide-graphene composite, pouring molten steel into a ladle, and then pouring them into a lost foam casting mold together, the casting temperature is 1570°C, after natural cooling and forming, a nano-particle reinforced carbon steel plate is obtained, the nano-particle reinforced carbon steel plate is placed in an annealing furnace, slowly heated to 860°C, kept warm for 3h, then cooled to 400°C with the furnace at a speed of 120°C / h, and then air-cooled to room temperature to obtain a carbon steel nanomaterial;
[0011] (4) The carbon steel nanomaterial is heated to 1100-1250°C, kept warm for 1-2 hours, and then hot-rolled at 1000-1100°C with a final rolling temperature of 800-950°C to obtain a hot-rolled carbon steel nanomaterial; the hot-rolled carbon steel nanomaterial is water-cooled to 400-600°C at a rate of 100-200°C / s by an ultra-fast cooling method; the water-cooled hot-rolled carbon steel nanomaterial is plastically deformed at 400-600°C, and then kept warm at 400-600°C for 10-120 minutes, and then air-cooled to room temperature to obtain a metal nanomaterial.
[0012] Furthermore, the catalyst in step (1) is aqueous ammonia with a mass concentration of 25-28%.
[0013] Furthermore, the freeze-drying temperature in step (1) is -40°C.
[0014] Furthermore, the pressure of the hydraulic press in step (2) is 70KN.
[0015] Furthermore, in the step (2), the pressure inside the high vacuum thermal explosion-hot pressing furnace is lower than 10 MPa.
[0016] Furthermore, in step (3), the size of the nanoparticle reinforced carbon steel plate is 600 mm×120 mm×25 mm.
[0017] Furthermore, in step (4), the cumulative reduction during hot rolling is 75-95%.
[0018] Furthermore, the amount of plastic deformation in step (4) is 2-10%.
[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0020] The present invention uses nano silicon dioxide-graphene composites and nano TiC-TiB2 particles as fillers to prepare carbon steel metal nano materials to achieve lightweight and radiation-resistant effects.
[0021] First, a filler made of a composite of graphene and silicon dioxide is added to a metal material. When the metal material is calcined at a high temperature, titanium dioxide reacts with aluminum to deoxidize and generate a silicon semiconductor, which synergizes with graphene to form a doping structure to achieve an anti-radiation effect. Nano-TiC-TiB2 particles are introduced into molten steel through an aluminum-based intermediate alloy, and nano-particle reinforced carbon steel is successfully prepared. During the process, the aluminum base and carbon steel fuse to further improve the radiation resistance of the metal nanomaterial. Since the melting point of the metal is lower than that of titanium carbide and titanium boride, a metal liquid phase is easily generated during the synthesis process, making the metal Nanomaterials are denser and thus have improved performance; at the same time, some nanoparticles can participate in the heterogeneous nucleation of austenite, improving its nucleation efficiency, while nanoparticles that do not participate in nucleation are adsorbed at the liquid-solid interface, hindering interface movement, inhibiting the growth of austenite dendrites, and refining the grains to achieve the effect of reducing Widmanstätten structure; during the solid-state phase transformation process, fine primary austenite, increased grain boundaries and nanoparticles can provide more nucleation sites for ferrite and cementite, and combine with graphene and silicon semiconductors to further refine the cast and annealed structures, reduce the density of the metal, but improve its mechanical properties.
[0022] Secondly, the ultra-fast cooling technology is used to strengthen the nanoparticles in carbon steel, which can further increase the dislocation density of the steel, promote the uniform nucleation of cementite, and achieve a more uniform dispersion of nano-scale cementite particles in the entire organization. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of a lightweight radiation-resistant metal nanomaterial for SAR payload prepared in the following examples are as follows:
[0025] Radiation resistance: The metal nanomaterial with a size of 600mm×120mm×25mm was fixed on the sample stage, and the S parameters were tested based on the waveguide method using a PNA-XN5244a network analyzer. The test range was 8.2GHz, 10.3GHz, and 12.4GHz; the total electromagnetic shielding efficiency (SE total )、Electromagnetic absorption loss (SE A ) and electromagnetic reflection loss (SE T ) is calculated by the following formula:
[0026] SE total(dB)=-10log[|S 21 | 2 ]
[0027] SE R =-10log(1-|S 11 | 2 )
[0028] SE A =-10log[|S 21 |2 / (1-|S 11 | 2 )]
[0029] Example 1
[0030] (1) adding 1 part of tetraethyl orthosilicate to 8 parts of ethanol aqueous solution with a mass fraction of 90% ethanol, then adding 0.5 parts of ammonia water with a mass concentration of 25% as a catalyst, and reacting at a temperature of 40° C. with a power of 30 kHz and a stirring speed of 200 rpm for 1 hour to obtain a nano-silica sol; adding 0.5 parts of graphene to 10 parts of the nano-silica sol, and stirring at a power of 30 kHz and a speed of 200 rpm for 1 hour to disperse evenly to obtain a mixed solution, and freeze-drying at -40° C. until no more weight loss occurs to obtain a nano-silica-graphene composite;
[0031] (2) Al powder, Ti powder and B4C powder with a purity of 99.5% were placed in a drying oven at a temperature of 950°C in a mass ratio of 74:20:8 for drying for 24 hours, and then the dried mixed powder was ball-milled and activated using a high-energy ball mill. 5 mm quartz stone was added as a ball-milling medium. The ball-to-material ratio was 10:1, the ball mill speed was 60 rpm, the forward and reverse switching time was 15 minutes, and the ball milling was carried out for 48 hours. The mixed powder was taken out and wrapped with aluminum foil. The coated mixed powder was pressed into a cylindrical block on a hydraulic press. The pressure of the hydraulic press was 70 KN, and the block size was 2.3 mm. The cylindrical blank is wrapped with graphite paper, and then placed in a graphite mold for in-situ reaction of the pressed green body sintering. The graphite mold is placed in a high vacuum thermal explosion-hot pressing furnace, the pressure in the furnace is lower than 10MPa, the temperature in the furnace is heated to 500°C, kept warm for 10 minutes, and then continued to heat to 900°C, kept warm for 10 minutes, and then an axial pressure of 40MPa is applied to the pressed green body, and the pressure is maintained for about 25 seconds; then the heating device is turned off, the vacuum in the furnace is maintained, and the furnace is cooled to room temperature to obtain an aluminum-based intermediate alloy containing nano-TiC-TiB2 particles;
[0032] (3) No. 35 steel and cold plate are placed in a 1000kg medium frequency induction furnace at a mass ratio of 3:5, heated to 1660°C, kept warm for 2 hours, and molten steel is obtained. Then, the ladle is preheated in advance, and the preheating temperature is 300°C; before pouring the ladle, an aluminum-based master alloy containing nano-TiC-TiB2 particles accounting for 0.1% by mass of No. 35 steel is crushed by a planer and evenly spread on the bottom of the ladle, and then nano-silicon dioxide-graphene accounting for 0.04% by mass of No. 35 steel is evenly sprinkled. The composite material is prepared by pouring molten steel into a ladle, and then pouring them into a lost foam casting mold together, with a casting temperature of 1570°C. After natural cooling and forming, a nanoparticle-reinforced carbon steel plate is obtained, and the steel plate size is 600mm×120mm×25mm. The nanoparticle-reinforced carbon steel plate is placed in an annealing furnace, slowly heated to 860°C, kept warm for 3h, then cooled to 400°C with the furnace at a speed of 120°C / h, and then air-cooled to room temperature to obtain a carbon steel nanomaterial;
[0033] (4) The carbon steel nanomaterial is heated to 1100°C, kept warm for 1 hour, and then hot-rolled at 1000°C with a cumulative reduction of 75% and a final rolling temperature of 800°C to obtain a hot-rolled carbon steel nanomaterial; the hot-rolled carbon steel nanomaterial is water-cooled to 400°C at a rate of 100°C / s using an ultra-fast cooling method; the water-cooled hot-rolled carbon steel nanomaterial is plastically deformed at 400°C with a deformation of 2%, and then kept warm at 400°C for 10 minutes, and then air-cooled to room temperature to obtain a metal nanomaterial.
[0034] Example 2
[0035] (1) adding 1 part of tetraethyl orthosilicate to 9 parts of ethanol aqueous solution with a mass fraction of 90% ethanol, then adding 0.6 parts of ammonia water with a mass concentration of 26% as a catalyst, and reacting at a temperature of 40° C. with a power of 30 kHz and a stirring speed of 200 rpm for 1 hour to obtain a nano-silica sol; adding 1 part of graphene to 10 parts of the nano-silica sol, and stirring at a power of 30 kHz and a speed of 200 rpm for 1 hour to disperse evenly to obtain a mixed solution, and freeze-drying at -40° C. until no more weight loss occurs to obtain a nano-silica-graphene composite;
[0036] (2) Al powder, Ti powder and B4C powder with a purity of 99.5% were placed in a drying oven at a temperature of 950°C in a mass ratio of 74:20:8 for drying for 24 hours, and then the dried mixed powder was ball-milled and activated using a high-energy ball mill. 5 mm quartz stone was added as a ball-milling medium. The ball-to-material ratio was 10:1, the ball mill speed was 60 rpm, the forward and reverse switching time was 15 minutes, and the ball milling was carried out for 48 hours. The mixed powder was taken out and wrapped with aluminum foil. The coated mixed powder was pressed into a cylindrical block on a hydraulic press. The pressure of the hydraulic press was 70 KN, and the block size was 2.3 mm. The cylindrical blank is wrapped with graphite paper, and then placed in a graphite mold for in-situ reaction of the pressed green body sintering. The graphite mold is placed in a high vacuum thermal explosion-hot pressing furnace, the pressure in the furnace is lower than 10MPa, the temperature in the furnace is heated to 500°C, kept warm for 10 minutes, and then continued to heat to 900°C, kept warm for 10 minutes, and then an axial pressure of 50MPa is applied to the pressed green body, and the pressure is maintained for about 25 seconds; then the heating device is turned off, the vacuum in the furnace is maintained, and the furnace is cooled to room temperature to obtain an aluminum-based intermediate alloy containing nano-TiC-TiB2 particles;
[0037] (3) No. 35 steel and cold plate are placed in a 1000kg medium frequency induction furnace at a mass ratio of 3:5, heated to 1660°C, kept warm for 2 hours, and molten steel is obtained. Then, the ladle is preheated in advance, and the preheating temperature is 300°C; before pouring the ladle, an aluminum-based master alloy containing nano-TiC-TiB2 particles accounting for 0.2% by mass of No. 35 steel is crushed by a planer and evenly spread on the bottom of the ladle, and then nano-silicon dioxide-graphite accounting for 0.044% by mass of No. 35 steel is evenly sprinkled. The olefin compound is poured into a ladle and then poured into a lost foam casting mold at a casting temperature of 1570°C. After natural cooling and forming, a nanoparticle-reinforced carbon steel plate is obtained. The steel plate size is 600mm×120mm×25mm. The nanoparticle-reinforced carbon steel plate is placed in an annealing furnace, slowly heated to 860°C, kept warm for 3h, then cooled to 400°C with the furnace at a rate of 120°C / h, and then air-cooled to room temperature to obtain a carbon steel nanomaterial.
[0038] (4) The carbon steel nanomaterial is heated to 1175°C, kept warm for 1.5 hours, and then hot-rolled at 1050°C with a cumulative reduction of 85% and a final rolling temperature of 875°C to obtain a hot-rolled carbon steel nanomaterial; the hot-rolled carbon steel nanomaterial is water-cooled to 500°C at a rate of 150°C / s using an ultra-fast cooling method; the water-cooled hot-rolled carbon steel nanomaterial is plastically deformed at 500°C with a deformation of 6%, and then kept warm at 500°C for 60 minutes, and then air-cooled to room temperature to obtain a metal nanomaterial.
[0039] Example 3
[0040] (1) adding 1 part of tetraethyl orthosilicate to 10 parts of ethanol aqueous solution with a mass fraction of 90% ethanol, then adding 0.7 parts of ammonia water with a mass concentration of 28% as a catalyst, and reacting at a temperature of 40° C. with a power of 30 kHz and a stirring speed of 200 rpm for 1 hour to obtain a nano-silica sol; adding 1.5 parts of graphene to 10 parts of the nano-silica sol, and stirring at a power of 30 kHz and a speed of 200 rpm for 1 hour to disperse evenly to obtain a mixed solution, and freeze-drying at -40° C. until no more weight loss occurs to obtain a nano-silica-graphene composite;
[0041] (2) Al powder, Ti powder and B4C powder with a purity of 99.5% were placed in a drying oven at a temperature of 950°C in a mass ratio of 74:20:8 for drying for 24 hours, and then the dried mixed powder was ball-milled and activated using a high-energy ball mill. 5 mm quartz stone was added as a ball-milling medium. The ball-to-material ratio was 10:1, the ball mill speed was 60 rpm, the forward and reverse switching time was 15 minutes, and the ball milling was carried out for 48 hours. The mixed powder was taken out and wrapped with aluminum foil. The coated mixed powder was pressed into a cylindrical block on a hydraulic press. The pressure of the hydraulic press was 70 KN, and the block size was 2.3 mm. The cylindrical blank is wrapped with graphite paper, and then placed in a graphite mold for in-situ reaction of the pressed green body sintering. The graphite mold is placed in a high vacuum thermal explosion-hot pressing furnace, the pressure in the furnace is lower than 10MPa, the temperature in the furnace is heated to 500°C, kept warm for 10 minutes, and then continued to heat to 900°C, kept warm for 10 minutes, and then an axial pressure of 60MPa is applied to the pressed green body, and the pressure is maintained for about 25 seconds; then the heating device is turned off, the vacuum in the furnace is maintained, and the furnace is cooled to room temperature to obtain an aluminum-based intermediate alloy containing nano-TiC-TiB2 particles;
[0042] (3) No. 35 steel and cold plate are placed in a 1000kg medium frequency induction furnace at a mass ratio of 3:5, heated to 1660°C, kept warm for 2 hours, and molten steel is obtained. Then, the ladle is preheated in advance, and the preheating temperature is 300°C; before pouring the ladle, an aluminum-based master alloy containing nano-TiC-TiB2 particles accounting for 0.3% of the mass ratio of No. 35 steel is crushed by a planer and evenly spread on the bottom of the ladle, and then nano-silicon dioxide-graphite accounting for 0.048% of the mass ratio of No. 35 steel is evenly sprinkled. The olefin compound is poured into a ladle and then poured into a lost foam casting mold at a casting temperature of 1570°C. After natural cooling and forming, a nanoparticle-reinforced carbon steel plate is obtained. The steel plate size is 600mm×120mm×25mm. The nanoparticle-reinforced carbon steel plate is placed in an annealing furnace, slowly heated to 860°C, kept warm for 3h, then cooled to 400°C with the furnace at a rate of 120°C / h, and then air-cooled to room temperature to obtain a carbon steel nanomaterial.
[0043] (4) The carbon steel nanomaterial is heated to 1250°C, kept warm for 2 hours, and then hot-rolled at 1100°C with a cumulative reduction of 95% and a final rolling temperature of 950°C to obtain a hot-rolled carbon steel nanomaterial; the hot-rolled carbon steel nanomaterial is water-cooled to 600°C at a rate of 200°C / s using an ultra-fast cooling method; the water-cooled hot-rolled carbon steel nanomaterial is plastically deformed at 600°C with a deformation of 10%, and then kept warm at 600°C for 120 minutes, and then air-cooled to room temperature to obtain a metal nanomaterial.
[0044] Comparative Example 1
[0045] The difference between Comparative Example 1 and Example 2 is that there is no step (1), and step (3) is changed to: No. 35 steel and cold plate are placed in a 1000kg medium frequency induction furnace at a mass ratio of 3:5, heated to 1660°C, kept warm for 2h, and molten steel is obtained, and then the ladle is preheated in advance, and the preheating temperature is 300°C; before pouring the ladle, an aluminum-based intermediate alloy containing nano-TiC-TiB2 particles accounting for 0.2% by mass of No. 35 steel is crushed by a planer and evenly spread on the bottom of the ladle, and then evenly sprinkled with 0.044% by mass of No. 35 steel The nano-scale graphene with a certain amount of ratio is poured into the ladle with molten steel, and then poured into the lost foam casting mold together. The casting temperature is 1570°C. After natural cooling and forming, a nanoparticle-reinforced carbon steel plate is obtained. The steel plate size is 600mm×120mm×25mm. The nanoparticle-reinforced carbon steel plate is placed in an annealing furnace, slowly heated to 860°C, kept warm for 3h, then cooled to 400°C with the furnace at a rate of 120°C / h, and then air-cooled to room temperature to obtain a carbon steel nanomaterial. The remaining steps are the same as those in Example 2.
[0046] Comparative Example 2
[0047] The difference between Comparative Example 2 and Example 2 lies in the difference in step (1) (3), whereby step (1) (3) is changed to: (1) adding 1 part of tetraethyl orthosilicate to 9 parts of ethanol aqueous solution having an ethanol mass fraction of 90%, and then adding 0.6 parts of ammonia water having a mass concentration of 26% as a catalyst, and reacting at a temperature of 40° C. with a power of 30 kHz and a stirring speed of 200 rpm for 1 h to obtain a nano-silica sol, and freeze-drying at -40° C. until no more weight loss occurs to obtain nano-silica;
[0048] (3) No. 35 steel and cold plate are placed in a 1000kg medium frequency induction furnace at a mass ratio of 3:5, heated to 1660°C, kept warm for 2 hours, and molten steel is obtained. Then, the ladle is preheated in advance, and the preheating temperature is 300°C; before pouring the ladle, an aluminum-based master alloy containing nano-TiC-TiB2 particles accounting for 0.2% by mass of No. 35 steel is crushed by a planer and evenly spread on the bottom of the ladle, and then nano-silicon dioxide accounting for 0.044% by mass of No. 35 steel is evenly sprinkled into the ladle. Pour in molten steel and then pour them into a lost foam casting mold together. The casting temperature is 1570°C. After natural cooling and forming, a nanoparticle-reinforced carbon steel plate is obtained. The steel plate size is 600mm×120mm×25mm. The nanoparticle-reinforced carbon steel plate is placed in an annealing furnace, slowly heated to 860°C, kept warm for 3h, then cooled to 400°C with the furnace at a rate of 120°C / h, and then air-cooled to room temperature to obtain a carbon steel nanomaterial. The remaining steps are the same as Example 2.
[0049] Comparative Example 3
[0050] The difference between Comparative Example 3 and Example 2 is that steps (2) and (3) are different. Steps (2) and (3) are changed to: (2) Al powder, Ti powder and B4C powder with a purity of 99.5% are placed in a drying oven at a temperature of 950°C in a mass ratio of 74:20:8 and dried for 24 hours. Then, the dried mixed powder is ball-milled and activated using a high-energy ball mill. 5 mm quartz stone is added as a ball-milling medium. The ball-to-material ratio is 10:1, the ball mill speed is 60 rpm, the forward and reverse conversion time is 15 minutes, and the ball milling is performed for 48 hours to obtain nano TiC-TiB2 particles.
[0051] (3) No. 35 steel and cold plate are placed in a 1000kg medium frequency induction furnace at a mass ratio of 3:5, heated to 1660°C, kept warm for 2h, and molten steel is obtained. Then the ladle is preheated in advance, and the preheating temperature is 300°C; before the ladle is poured, nano TiC-TiB2 particles accounting for 0.2% of the mass ratio of No. 35 steel are uniformly sprinkled with nano silicon dioxide-graphene composites accounting for 0.044% of the mass ratio of No. 35 steel, and molten steel is poured into the ladle, and then poured into the lost foam casting mold together, the casting temperature is 1570°C, and after natural cooling and forming, a nano particle reinforced carbon steel plate is obtained, the steel plate size is 600mm×120mm×25mm, the nano particle reinforced carbon steel plate is placed in an annealing furnace, slowly heated to 860°C, kept warm for 3h, then cooled to 400°C with the furnace at a rate of 120°C / h, and then air cooled to room temperature to obtain a carbon steel nano material; the remaining steps are the same as those in Example 2.
[0052] Comparative Example 4
[0053] The difference between Comparative Example 4 and Example 2 is that there is no step (2), and step (3) is changed to: No. 35 steel and cold plate are placed in a 1000kg medium frequency induction furnace at a mass ratio of 3:5, heated to 1660°C, kept warm for 2h, and molten steel is obtained, and then the ladle is preheated in advance, and the preheating temperature is 300°C; before pouring the ladle, the aluminum foil accounting for 0.2% of the mass ratio of No. 35 steel is crushed by a planer and evenly spread on the bottom of the ladle, and then the nano-silicon dioxide-graphene accounting for 0.044% of the mass ratio of No. 35 steel is evenly sprinkled The composite material is prepared by pouring molten steel into a ladle, and then pouring them into a lost foam casting mold together. The casting temperature is 1570°C. After natural cooling and forming, a nanoparticle-reinforced carbon steel plate is obtained. The steel plate size is 600mm×120mm×25mm. The nanoparticle-reinforced carbon steel plate is placed in an annealing furnace, slowly heated to 860°C, kept warm for 3h, then cooled to 400°C with the furnace at a rate of 120°C / h, and then air-cooled to room temperature to obtain a carbon steel nanomaterial. The remaining steps are the same as those in Example 2.
[0054] Comparative Example 5
[0055] The difference between Comparative Example 5 and Example 2 is that there is no step (4), and step (3) is changed to: No. 35 steel and cold plate are placed in a 1000kg medium frequency induction furnace at a mass ratio of 3:5, heated to 1660°C, kept warm for 2h, and molten steel is obtained, and then the ladle is preheated in advance, and the preheating temperature is 300°C; before pouring the ladle, an aluminum-based intermediate alloy containing nano-TiC-TiB2 particles accounting for 0.2% by mass of No. 35 steel is crushed by a planer and evenly spread on the bottom of the ladle, and then 0.044% by mass of No. 35 steel is evenly sprinkled A nano-silicon dioxide-graphene composite is prepared by pouring molten steel into a ladle, and then pouring the molten steel into a lost foam casting mold together. The casting temperature is 1570°C. After natural cooling and forming, a nano-particle reinforced carbon steel plate is obtained. The steel plate has a size of 600mm×120mm×25mm. The nano-particle reinforced carbon steel plate is placed in an annealing furnace, slowly heated to 860°C, kept warm for 3h, then cooled to 400°C with the furnace at a rate of 120°C / h, and then air-cooled to room temperature to obtain a metal nano-material. The remaining steps are the same as those in Example 2.
[0056] Effect example
[0057] Table 1 below shows the performance analysis results of a lightweight radiation-resistant metal nanomaterial for SAR payload using Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0058] Table 1
[0059]
[0060] From the comparison of the experimental data of radiation resistance of the embodiment and the comparative example, it can be found that the filler composed of graphene and silicon dioxide is added to the metal material in the present invention. When the metal material is calcined at high temperature, titanium dioxide reacts with aluminum to deoxidize and generate silicon semiconductor, and forms a doping structure with graphene to achieve the effect of radiation resistance. Nano-TiC-TiB2 particles are introduced into molten steel through aluminum-based intermediate alloys to successfully prepare nano-particle reinforced carbon steel. In the process, the aluminum base and carbon steel are fused to further improve the radiation resistance of the metal nanomaterial. Since the melting point of the metal is lower than that of titanium carbide and titanium boride, it is easy to resist the radiation during the synthesis process. It is easy to generate a metal liquid phase, making the metal nanomaterial more compact and thus improving its performance; at the same time, some nanoparticles can participate in the heterogeneous nucleation of austenite, improving its nucleation efficiency, while the nanoparticles that do not participate in nucleation are adsorbed on the liquid-solid interface, hindering the interface movement, inhibiting the growth of austenite dendrites, and refining the grains to achieve the effect of reducing the Widmanstätten structure; during the solid-state phase transformation process, the fine primary austenite, increased grain boundaries and nanoparticles can provide more nucleation sites for ferrite and cementite, and combine with graphene and silicon semiconductors to further refine the cast and annealed structures, reduce the density of the metal, but improve its mechanical properties. The use of ultra-fast cooling technology to strengthen the nanoparticles in carbon steel can further increase the dislocation density of the steel, promote the uniform nucleation of cementite, and achieve a more uniform dispersion of nano-scale cementite particles throughout the entire organization.
[0061] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A lightweight radiation-resistant metal nanomaterial for SAR payload, characterized in that: The metal nano material is a carbon steel nano material prepared by taking nano silicon dioxide-graphene composite and nano TiC-TiB2 particles as fillers.
2. The lightweight radiation-resistant metal nanomaterial for SAR payload according to claim 1, characterized in that: The nano silicon dioxide-graphene composite is prepared by reducing tetraethyl orthosilicate to silicon dioxide sol and graphene, and is reduced to silicon semiconductor at high temperature when preparing carbon steel material.
3. A method for preparing a lightweight radiation-resistant metal nanomaterial for SAR payload, characterized in that: The method comprises the following preparation steps: (1) adding 1 part of ethyl orthosilicate to 8-10 parts of ethanol aqueous solution with a mass fraction of 90% ethanol, then adding 0.5-0.7 parts of a catalyst, and reacting at a temperature of 40° C. with a power of 30 kHz and a stirring speed of 200 rpm for 1 hour to obtain a nano-silica sol; adding 0.5-1.5 parts of graphene to 10 parts of the nano-silica sol, and stirring at a power of 30 kHz and a speed of 200 rpm for 1 hour to disperse evenly to obtain a mixed solution, and freeze-drying until no more weight loss occurs to obtain a nano-silica-graphene composite; (2) Al powder, Ti powder and B4C powder with a purity of 99.5% were placed in a drying oven at a temperature of 950°C in a mass ratio of 74:20:8 for drying for 24 hours, and then the dried mixed powder was ball-milled and activated using a high-energy ball mill. 5 mm quartz stone was added as a ball-milling medium, the ball-to-material ratio was 10:1, the ball mill speed was 60 rpm, the forward and reverse switching time was 15 minutes, and the ball milling was carried out for 48 hours; the mixed powder was taken out, wrapped with aluminum foil, and the coated mixed powder was pressed into a cylindrical block on a hydraulic press. The block size is φ30mm×32mm; the cylindrical green block is wrapped with graphite paper, and then placed in a graphite mold for in-situ reaction of green compact sintering, and the graphite mold is placed in a high vacuum thermal explosion-hot pressing furnace; the temperature in the furnace is heated to 500°C, kept warm for 10 minutes, and then continued to heat to 900°C, kept warm for 10 minutes, and then an axial pressure of 40-60MPa is applied to the green compact, and the pressure is maintained for about 25 seconds; then the heating device is turned off, the vacuum in the furnace is maintained, and the green compact is cooled to room temperature with the furnace to obtain an aluminum-based intermediate alloy containing nano-TiC-TiB2 particles; (3) No. 35 steel and cold plate are placed in a 1000kg medium frequency induction furnace at a mass ratio of 3:5, heated to 1660°C, kept warm for 2 hours, and molten steel is obtained. Then, the ladle is preheated in advance at a preheating temperature of 300°C. Before pouring the ladle, an aluminum-based master alloy containing nano-TiC-TiB2 particles accounting for 0.1-0.3% of the mass of No. 35 steel is crushed by a planer and evenly spread on the bottom of the ladle, and then evenly sprinkled into the ladle at a mass ratio of 0.04-0.04 8% by mass ratio of nano-silicon dioxide-graphene composite, pouring molten steel into a ladle, and then pouring them into a lost foam casting mold together, the casting temperature is 1570°C, after natural cooling and forming, a nano-particle reinforced carbon steel plate is obtained, the nano-particle reinforced carbon steel plate is placed in an annealing furnace, slowly heated to 860°C, kept warm for 3h, then cooled to 400°C with the furnace at a speed of 120°C / h, and then air-cooled to room temperature to obtain a carbon steel nanomaterial; (4) The carbon steel nanomaterial is heated to 1100-1250°C, kept warm for 1-2 hours, and then hot-rolled at 1000-1100°C with a final rolling temperature of 800-950°C to obtain a hot-rolled carbon steel nanomaterial; the hot-rolled carbon steel nanomaterial is water-cooled to 400-600°C at a rate of 100-200°C / s by an ultra-fast cooling method; the water-cooled hot-rolled carbon steel nanomaterial is plastically deformed at 400-600°C, and then kept warm at 400-600°C for 10-120 minutes, and then air-cooled to room temperature to obtain a metal nanomaterial.
4. The method for preparing a lightweight radiation-resistant metal nanomaterial for SAR payload according to claim 3, characterized in that: The catalyst in step (1) is aqueous ammonia with a mass concentration of 25-28%.
5. The method for preparing a lightweight radiation-resistant metal nanomaterial for SAR payload according to claim 3, characterized in that: The freeze-drying temperature in step (1) is -40°C.
6. The method for preparing a lightweight radiation-resistant metal nanomaterial for SAR payload according to claim 3, characterized in that: The pressure of the hydraulic press in step (2) is 70KN.
7. The method for preparing a lightweight radiation-resistant metal nanomaterial for SAR payload according to claim 3, characterized in that: In the step (2), the pressure inside the high vacuum thermal explosion-hot pressing furnace is lower than 10 MPa.
8. The method for preparing a lightweight radiation-resistant metal nanomaterial for SAR payload according to claim 3, characterized in that: In the step (3), the size of the nanoparticle reinforced carbon steel plate is 600 mm×120 mm×25 mm.
9. The method for preparing a lightweight radiation-resistant metal nanomaterial for SAR payload according to claim 3, characterized in that: The cumulative reduction during hot rolling in step (4) is 75-95%.
10. The method for preparing a lightweight radiation-resistant metal nanomaterial for SAR payload according to claim 3, characterized in that: The amount of plastic deformation in step (4) is 2-10%.